Desarrollo de la plataforma de capacitación para los alumnos de la carrera de Sistemas de Información de La Universidad Técnica de Cotopaxi Extensión La Maná con integración a la app android de servicios. - Cuichan Simbaña, Darwin Alexis (2021)
The present investigation consists of the development and implementation of a training platform for the students of the Information Systems Major of the Technical University of Cotopaxi in La Maná with integration to the Android App of services, for the realization of this, we proceeded to verify how the processes of sending and receiving tasks as well as the area of linking with society are currently carried out, with the platform is intended to facilitate access to information anywhere and at any time and thus to streamline management processes allowing administrative change parameters that are currently carried. It is of great support for higher institutions to have a platform that allows them to carry out academic processes in accordance with technological advances and with access to fast and concrete services. With the development of the training platform, students will be able to complement their training at all levels of study, promoting for this purpose an alliance with linkage projects that can develop the contents and manage the platform over time. This platform will keep a record of the progress of the participants and will socialize through the App the status of each course taken and alerts to keep the student on track in the execution of the same.